Sjögren Syndrome Complicated with Cystic Lung Disease and Pulmonary Amyloidosis - Koichiro Takahashi; Hironori Sadamatsu; Shinsuke Ogusu; Kazutoshi Komiya; Tomomi Nakamura; Shinya Kimura; Naoko Sueoka-Aragane (Case Reports in Rheumatology)
A 72-year-old Japanese woman was noted to have multiple cystic lung shadows and infiltrates on chest radiography and computed tomography (CT). She complained of dryness of the mouth and eyes, but she did not have respiratory symptoms, such as cough, sputum production, and dyspnea. Her laboratory findings showed high titers of anti-SSA/Ro and anti-SSB/La antibodies. Surgical lung biopsy was performed and demonstrated pathologic findings of amyloid light-chain deposition and bronchiolitis with lymphocytic infiltration. Taken altogether, she was diagnosed as Sjögren syndrome with bronchiolitis and pulmonary amyloidosis. Since then, she has been carefully followed up without treatment. After 6 years, the cystic lung lesions on CT gradually enlarged and increased in number, but she remained to have no respiratory symptoms and no manifestations of lymphoma. Here, we report a rare case of Sjögren syndrome complicated with cystic lung disease and pulmonary amyloidosis.